Application of active thermography for defectoscopy of technological equipment on objects of the nuclear power plants - Bazaleev, N.I.; Lytvynenko, V.V. (Вопросы атомной науки и техники, 2019)
The methodical and physical bases of the use of active thermography as a high-performance non-destructive method of control and defectoscopy of materials during thermovision monitoring of technological equipment at NPP objects are considered. The data of experimental research confirm the efficiency of the use of thermal and low-frequency electromagnetic activators in the thermographic defectoscopy. The features of the application of dynamic thermography and the influence of external activation sources on the thermal appearance of structural inhomogeneities and defects in materials are investigated. It is shown that the application of special methods of processing thermal images that take into account the amplitude-frequency and morphological features of thermoanomalies, allows to control the thermal display of energy-absorbing structures and defects, provide the possibility of their identification against the background of false thermoanomalies.